Homotypic aggregation and terminal glycosylation of cells from dissociated human colorectal tumor tissue - Kemmner, Wolfram A.; Schlag, Peter M.; Möller, Peter; Brossmer, Reinhard (Oncology, 1992)
Colorectal tumor tissue directly obtained from the surgeon was dissociated by enzymatical and mechanical disruption into a suspension of single cells of high viability. Homotypic aggregation, sialidase-accessible sialic acid and total fucose content of tumor cells were determined. Aggregation of cells from mucinous tumors was found to be significantly lower than of cells from nonmucinous tissue. The median value of surface-bound sialic acid was lower in strongly aggregating cells compared to nonaggregating cells. Cells from metastasizing tumors showed slightly lower aggregation, but on an average carried more surface-bound sialic acid and were significantly higher fucosylated than cells from nonmetastasizing tumors.
Elektronische Reproduktion der Druck-Ausgabe 26. Juni 2009
Gesehen am 25.06.2024
Falsche Namensform in der Verantwortlichkeitsangabe. Richtig: Schlag, P